2005
DOI: 10.1111/j.1529-8817.2005.04132.x
|View full text |Cite
|
Sign up to set email alerts
|

COMBINING NEW TECHNOLOGIES FOR DETERMINATION OF PHYTOPLANKTON COMMUNITY STRUCTURE IN THE NORTHERN GULF OF MEXICO 1

Abstract: In situ analysis of phytoplankton community structure was determined at five stations along the Texas Gulf coast using two instruments, the Fluoroprobe and FlowCAM. Results were compared with traditional methods to determine community structure (pigment analysis and microscopy). Diatoms and small nanoplankton (most likely haptophytes) dominated the phytoplankton community at all stations. Estimated chl concentrations for diatoms+dinoflagellates obtained via the Fluoroprobe were not significantly different for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 20 publications
4
40
1
1
Order By: Relevance
“…For larger cells (greater than ∼10 μm in size) from morphologically distinct populations, imaging cytometry is preferred. This method marries microscope-like optical (i.e., visual) characterization with a flow cytometry-like sample stream, thus providing much higher throughput than standard microscopic analysis (See et al 2005, Sieracki et al 1998. Pictures (or other optical information like fluorescence) are obtained from each cell as it crosses the imaging point, and the cells are later identified either manually or automatically based on training data sets.…”
Section: Orthogonal (90°) Scattermentioning
confidence: 99%
“…For larger cells (greater than ∼10 μm in size) from morphologically distinct populations, imaging cytometry is preferred. This method marries microscope-like optical (i.e., visual) characterization with a flow cytometry-like sample stream, thus providing much higher throughput than standard microscopic analysis (See et al 2005, Sieracki et al 1998. Pictures (or other optical information like fluorescence) are obtained from each cell as it crosses the imaging point, and the cells are later identified either manually or automatically based on training data sets.…”
Section: Orthogonal (90°) Scattermentioning
confidence: 99%
“…Improving early detection has therefore been identified as a priority for HAB research and management, as well as ocean monitoring in general (HARRNESS 2005; U.S. Commission on Ocean Policy 2004; NSTC Joint Subcommittee on Ocean Science and Technology 2007). This priority has catalyzed the development of a number of fielddeployable systems for the detection and monitoring of various phytoplankton and HAB species (e.g., Babin et al 2005;See et al 2005;Casper et al 2007;Duy and Connell 2007). Some examples include imaging flow systems (Sieracki et al Field applications of the second-generation Environmental Sample Processor (ESP) for remote detection of harmful algae:…”
Section: Introductionmentioning
confidence: 99%
“…This is a desirable characteristic that allows a direct estimation of the degree of local spectral dominance without the requirement of bio-volume transformations from biomass information. Previous studies on the comparison of different techniques for assessing phytoplankton community structures have shown that FluoroProbe is potentially capable of determining its general characteristics when compared to HPLC analyses [47][48][49]. However, its application improves greatly when species-specific calibrations under different environmental conditions are considered [49].…”
Section: Discussionmentioning
confidence: 99%